2018
DOI: 10.1164/rccm.201805-0986st
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Coexisting Chronic Illness into Decisions about Patient Selection for Lung Cancer Screening. An Official American Thoracic Society Research Statement

Abstract: There is an urgent need for further research that can help guide clinical decision-making with patients who may not benefit from LCS owing to coexisting chronic illness. This statement establishes a research framework to address essential questions regarding how to incorporate and communicate risks of comorbidities into patient selection and decisions regarding LCS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 49 publications
1
58
0
5
Order By: Relevance
“…Calculating risk does not obviate the need to assess whether a patient is sufficiently healthy to tolerate complications from either follow-up of LCS-detected cancer or lung cancer treatment. Ideally, to be most useful for selecting optimal candidates for LCS in clinical practice, risk calculators should be coupled with modeling analysis that take into account competing risks and causes of death and the individual’s ability to undergo invasive evaluation of screen-detected nodules or lung cancer treatment ( 95 ).…”
Section: Resultsmentioning
confidence: 99%
“…Calculating risk does not obviate the need to assess whether a patient is sufficiently healthy to tolerate complications from either follow-up of LCS-detected cancer or lung cancer treatment. Ideally, to be most useful for selecting optimal candidates for LCS in clinical practice, risk calculators should be coupled with modeling analysis that take into account competing risks and causes of death and the individual’s ability to undergo invasive evaluation of screen-detected nodules or lung cancer treatment ( 95 ).…”
Section: Resultsmentioning
confidence: 99%
“…Lifegained-based selection could also unify the metrics for cancer screening across stakeholders -patients, clinicians, cost-effectiveness modelers (35,36), and guidelines committees (28,37). Importantly, our proposed life-gained-based strategy could readily address two key issues facing population-wide cancer screening-ages at initiation/cessation of screening (38) and the identification of individuals for whom the benefits of screening outweigh its harms (14)(15)(16)(17). In contrast to risk-based selection, a life-gained-based selection circumvents the need for ages at initiation/cessation of screening because it naturally excludes individuals without both high-enough disease-risk to benefit from screening and high-enough lifeexpectancy to gain life-years from screening, regardless of age.…”
Section: Discussionmentioning
confidence: 99%
“…However, preventing more lung cancer deaths may not always translate to substantial gains in life-expectancy. Such risk-based screening-selection would preferentially include older heavy-smokers with multiple co-morbidities who have reduced life-expectancy, and consequently, reduced life-gained from screening (14)(15)(16)(17)(18). Indeed, recent microsimulation analyses have shown that, while using risk-prediction models can further reduce lung cancer deaths, the life-years gained may be more modest (19) and that unless high risk patients also have sufficiently long life-expectancy, patients may not experience a net benefit from screening (20).…”
Section: Introductionmentioning
confidence: 99%
“…The latter judgment is actually subjective and the keystone is to mimic the entry criteria of clinical trials. Models predicting competing causes of death and suggesting exclusion from screening or curative intent treatments are being developed: although they may prove useful to identify and manage (not over-treating) unlikely-to-benefit patients, they could lead to length time bias (overdiagnosis) [45][46][47].…”
Section: Selection Of High-risk Individuals For Ldct-lcsmentioning
confidence: 99%